Manufacturing process for improving uniformity of glass wool
By implementing strict raw material pretreatment and precise process parameter regulation in the glass wool production process, the problem of difficulty in meeting the uniformity of glass wool is solved, the high uniformity and high performance of glass wool is achieved, and its application scenarios are expanded.
Patent Information
- Application Number
- CN202510078985.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-11
AI Technical Summary
In the existing glass wool production process, the raw materials are not purified and contain impurities, which makes it difficult to meet the uniformity of glass wool products, affecting performance and application scenarios.
Strict raw material selection and pretreatment processes, including screening, magnetic separation, cleaning and drying, ensure the chemical purity and particle size uniformity of the raw materials. Then, during the heating, stirring, melting and fibrosis, through precise parameter regulation and special equipment structure, uniform mixing and stable fibrosis of the glass liquid can be achieved, and uniform molding of the glass wool can be achieved in the cotton collection forming stage.
Through this process, the uniformity of glass wool is significantly improved, the performance stability of the product is enhanced, the strict demand for glass wool quality in high-end applications, and the application scenarios of glass wool in various fields are broadened.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass wool, and in particular relates to a production process for improving the uniformity of glass wool. Background Art
[0002] As an important thermal insulation, heat insulation and sound absorption material, glass wool is widely used in many fields such as construction, industrial pipe insulation, and automobile manufacturing, and its market demand continues to rise. However, the current glass wool production process has significant defects, which makes it difficult to meet the product uniformity standards, seriously restricting the full performance of glass wool and the expansion of application scenarios.
[0003] In the raw material link, if the basic raw materials such as silica sand, soda ash, borax, alumina and broken glass are of low purity, contain impurities, or have uneven particle sizes, it is like mixing "inferior products" into the cornerstone of a building. No matter how finely processed it is, it is very easy to cause local performance differences in glass wool products. For example, silica sand with a lot of impurities may cause uneven hardness distribution of glass wool, affecting the stability of the overall structure; raw materials with large particle size differences are difficult to disperse evenly when mixed, which buries hidden dangers for subsequent processes.
[0004] The traditional preliminary screening process often selects the screen randomly and lacks precise adaptation to the characteristics of different raw materials, so that large particles of impurities and agglomerates cannot be completely removed, resulting in poor initial uniformity of the raw materials. The lack of magnetic separation or inaccurate control of magnetic field strength will miss magnetic metal impurities. When such impurities are melted at high temperatures, they may catalyze abnormal chemical reactions, causing uneven glass liquid composition, and ultimately unstable glass wool product quality; if the cleaning process only relies on simple soaking and stirring, it is difficult to remove stubbornly attached dust and salt. Without ultrasonic assistance, the cleaning effect is greatly reduced, and non-magnetic impurities remain on the surface of the raw materials, interfering with the uniform fusion of raw materials in subsequent processes. If the drying process heats up too quickly and the temperature is improperly controlled, the raw materials are prone to cracking or insufficient drying. Raw materials with too high moisture content enter the subsequent process, which will also destroy the process stability and affect the uniformity of glass wool; if the material conveying link is not accurate and uniform, problems such as raw material accumulation and proportion deviation will follow, causing the initial state of stirring to deviate from the track of uniform mixing.
[0005] In summary, the existing glass wool production process is in urgent need of improvement. Based on the above problems, the present invention proposes a systematic and sophisticated production process to comprehensively improve the uniformity of glass wool and meet the growing demand for high-quality glass wool in various fields. Summary of the invention
[0006] The object of the present invention is to provide a manufacturing process for improving the uniformity of glass wool, so as to solve the problems raised in the above-mentioned background technology.
[0007] To achieve the above object, the present invention provides the following technical solution: a production process for improving the uniformity of glass wool, comprising the following steps:
[0008] S1. Raw material selection: Weigh silica sand, soda ash, borax, alumina, and broken glass as basic raw materials. The purity of the selected silica sand is not less than 95%, the purity of soda ash is not less than 98%, the purity of borax is not less than 96%, the purity of alumina is not less than 97%, and the broken glass has no obvious discoloration and impurity agglomeration phenomenon;
[0009] S2. Preliminary screening: Place the silica sand raw material on a vibrating screen and select a sieve for the first screening to remove large particle impurities and agglomerates whose particle size is larger than the sieve aperture; screen soda ash, borax, alumina, and broken glass;
[0010] S3. Magnetic separation and impurity removal: The various raw materials that have been preliminarily screened are transported to the magnetic separator in sequence to adsorb and remove the mixed magnetic metal impurities in the raw materials to ensure the chemical purity of the raw materials;
[0011] S4. Cleaning step: Place the raw materials after magnetic separation in separate cleaning tanks, pour deionized water as the cleaning liquid, and control the mass ratio of deionized water to each raw material at 4:1. Turn on the stirring device for stirring, and apply ultrasonic cleaning to remove non-magnetic impurities such as dust and salt attached to the surface of the raw materials;
[0012] S4. After cleaning, the wet raw material is transferred to a hot air drying oven for moisture drying, thereby completing the raw material pretreatment;
[0013] S5. The silica sand, soda ash, borax, alumina and broken glass raw materials that have undergone the raw material pretreatment step are uniformly and accurately fed into a closed stirring kettle with heating and stirring functions through an automated material conveying system according to a predetermined ratio;
[0014] S6. Heating: Turn on the heating device of the stirring tank to steadily increase the temperature inside the stirring tank until it reaches 280-330°C. This heating process is monitored by a temperature sensor;
[0015] S7. Stirring operation: When the temperature is stable, the stirring blade of the stirring device is started to rotate at a constant speed, and continuous stirring operation is performed. During the mixing and stirring process, an inert gas is continuously introduced into the stirring tank to maintain a slightly positive pressure environment in the tank, and the pressure value is 0.01-0.03MPa higher than the external environment;
[0016] Preferably, in step S7, the surface of the stirring blade is covered with a ceramic wear-resistant coating with a thickness of 0.3-0.7 mm, the raw materials of the coating include silicon carbide and titanium dioxide in a mass ratio of 3:1, and the coating is attached to the blade by a plasma spraying process.
[0017] Preferably, according to step S7, the raw materials that have been stirred and mixed evenly are transported into a furnace, the furnace is heated by gas, the gas flow rate is accurately controlled at 10-20 cubic meters per hour, the temperature is raised to 1320-1420° C. at a rate of 12-18° C. per minute, 2%-5% of the total mass of the raw materials is added as a flux, and the temperature is kept for 1.8-2.8 hours to fully melt the raw materials into glass liquid, and the flux is a mixture of calcium fluoride and potassium nitrate in a mass ratio of 1:1.
[0018] Preferably, the lining of the furnace adopts a multi-layer composite structure, which includes high-alumina bricks, lightweight clay bricks, and rock wool insulation felt from the inside to the outside, with the thickness ratio of each layer being 1:1.5:2, and a high-temperature resistant adhesive is applied at the joints between the high-alumina bricks and the lightweight clay bricks.
[0019] Preferably, after melting is completed, the fiberization treatment step is entered, and the glass liquid is fiberized by centrifugal blowing. The speed of the centrifugal disk is controlled at 5200-6200 rpm, and the blowing air pressure is maintained at 0.35-0.55 MPa. At the same time, an annular air distribution plate is set in the blowing area, and ventilation holes with a diameter of 3-5 mm are distributed on the air distribution plate.
[0020] Preferably, the centrifugal disk is made of nickel-based high-temperature alloy, and its surface is electrolytically polished, with a surface roughness Ra < 0.5 microns. A guide groove is provided on the edge of the centrifugal disk, and the depth of the groove is 3-5 mm.
[0021] Preferably, in the fiberization treatment, the sprayed gas is purified air preheated to 220-320° C., the humidity of the sprayed gas is controlled at 5%-10%, and the sprayed gas is first filtered through a ceramic filter element with a pore size of 0.1-0.3 μm.
[0022] Preferably, the fiberization treatment is followed by a cotton collection and molding step, in which the fiberized glass wool is collected onto a uniformly moving molding mesh belt through negative pressure suction, the molding mesh belt speed is set to 6-12 m / min, the molding mesh belt surface has a micro-pit texture, the pit diameter is 0.5-1 mm, and an adjustable angle wind knife is arranged under the molding mesh belt, and the air flow temperature blown out by the wind knife is 80-120°C.
[0023] Preferably, in step S2, the silica sand raw material is screened with a 80-100 mesh screen; the soda ash is screened with a 60-80 mesh screen; the borax is processed with a 100-120 mesh screen; the alumina is screened with a 120-140 mesh screen; and the broken glass is screened with a 40-60 mesh screen.
[0024] Preferably, in step S4, the drying temperature of the drying box is increased from 80°C to 110°C at a heating rate of 5-10°C / min, and is kept at 110°C for 10-15 minutes until the moisture content of the raw material is lower than 0.8%.
[0025] Compared with the prior art, the technical effects and advantages of the present invention are as follows: the manufacturing process for improving the uniformity of glass wool,
[0026] The manufacturing process of the present invention effectively improves the uniformity of glass wool. On the one hand, starting from raw material processing, strict material selection, fine screening of impurities, deep purification and precise drying are carried out to ensure the uniform quality of raw materials in all aspects, lay a solid foundation for subsequent processes, and avoid product unevenness caused by raw material differences. On the other hand, in each link of heating, stirring, melting, fiberization to cotton collection and molding, precise parameter control, special equipment structure and suitable environment creation promote uniform mixing and stable fiberization of glass liquid, and finally make the fiber distribution of glass wool uniform during molding, which greatly enhances the uniformity of product and meets the stringent requirements of high-end applications for glass wool quality. When glass wool is used in various fields, it can fully exert its thermal insulation, heat insulation and sound absorption performance, broaden the application scenarios, and comply with the market demand for high-quality glass wool. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The present invention provides a technical solution: a production process for improving the uniformity of glass wool, comprising the following steps:
[0029] S1. Raw material selection: Silica sand, soda ash, borax, alumina and broken glass are weighed as basic raw materials by mass. The purity of the selected silica sand is not less than 95%, and its silicon dioxide content dominates the basic skeleton structure and hardness of the glass wool; the purity of soda ash is not less than 98%, and as a flux, it can effectively reduce the melting point of the glass liquid; the purity of borax is not less than 96%, which can improve the chemical stability and heat resistance of the glass; the purity of alumina is not less than 97%, and the broken glass has no obvious discoloration and impurity agglomeration phenomenon, which plays a role in enhancing the toughness of the glass fiber; the broken glass has no obvious discoloration and impurity agglomeration phenomenon, and can serve as part of the raw materials to reduce energy consumption;
[0030] S2. Preliminary screening: Place the silica sand raw material on a vibrating screen and select a sieve for the first screening to remove large particle impurities and agglomerates whose particle size is larger than the sieve aperture; screen soda ash, borax, alumina, and broken glass;
[0031] Silica sand raw materials are screened with 80-100 mesh screen; soda ash is screened with 60-80 mesh screen; borax is processed with 100-120 mesh screen; alumina is screened with 120-140 mesh screen; broken glass is screened with 40-60 mesh screen;
[0032] S3. Magnetic separation and impurity removal: The various raw materials that have been preliminarily screened are transported to the magnetic separator in sequence to adsorb and remove the mixed magnetic metal impurities in the raw materials to ensure the chemical purity of the raw materials;
[0033] The magnetic field strength of the magnetic separator is stably maintained at 9000-11000 Gauss. Under this magnetic field strength, it can accurately adsorb and remove magnetic metal impurities such as iron filings mixed in the raw materials, avoiding these impurities from causing crystallization and discoloration of the glass liquid in the subsequent high-temperature process.
[0034] S4. Cleaning step: Place the raw materials after magnetic separation in separate cleaning tanks, pour deionized water as the cleaning liquid, and control the mass ratio of deionized water to each raw material at 4:1. Turn on the stirring device for stirring, and apply ultrasonic cleaning to remove non-magnetic impurities such as dust and salt attached to the surface of the raw materials;
[0035] A stirring device is used to stir at a speed of 30-50 rpm to ensure that the raw material is fully in contact with the cleaning liquid. At the same time, ultrasonic waves are applied to assist cleaning. The ultrasonic frequency is set to 2-30kHz and the cleaning time is 20-25 minutes.
[0036] S4. After cleaning, the wet raw material is transferred to a hot air drying oven for moisture drying, thereby completing the raw material pretreatment;
[0037] The drying temperature starts at 80℃ and rises steadily to 110℃ at a rate of 5-10℃ / min, and then is kept at 110℃ for 10-15 minutes. This step-by-step heating helps prevent the raw materials from being damaged by cracking due to rapid heating until the moisture content of the raw materials is less than 0.8%
[0038] S5. The silica sand, soda ash, borax, alumina and broken glass raw materials that have undergone the raw material pretreatment step are uniformly and accurately fed into a closed stirring kettle with heating and stirring functions through an automated material conveying system according to a predetermined ratio;
[0039] According to the established ratio, the material is conveyed at a speed of 5-10 kg / min through an automated material conveying system to prevent the accumulation of raw materials at the inlet and ensure the uniformity of subsequent mixing.
[0040] S6. Heating: Turn on the heating device of the stirring tank to steadily increase the temperature inside the stirring tank until it reaches 280-330°C. This heating process is monitored by a temperature sensor;
[0041] The internal temperature of the stirred tank is steadily increased at a rate of 10-15°C / minute. This heating process is monitored in real time by a temperature sensor with an accuracy of ±0.5°C to accurately control the temperature and avoid affecting the reaction process of the raw materials due to too fast or too slow heating;
[0042] S7. Stirring operation: When the temperature is stable, the stirring blade of the stirring device is started to rotate at a constant speed, and continuous stirring operation is performed. During the mixing and stirring process, an inert gas is continuously introduced into the stirring tank to maintain a slightly positive pressure environment in the tank, and the pressure value is 0.01-0.03MPa higher than the external environment;
[0043] The surface of the stirring blade is covered with a ceramic wear-resistant coating with a thickness of 0.3-0.7 mm. The raw materials of the coating contain silicon carbide and titanium dioxide with a mass ratio of 3:1. The coating is attached to the blade by plasma spraying process.
[0044] The stirred and mixed raw materials are transported into the furnace. The furnace is heated by gas, and the gas flow rate is accurately controlled at 10-20 cubic meters / hour. The temperature is raised to 1320-1420°C at a rate of 12-18°C / minute. A flux accounting for 2%-5% of the total mass of the raw materials is added and kept warm for 1.8-2.8 hours to fully melt the raw materials into glass liquid. The flux is a mixture of calcium fluoride and potassium nitrate in a 1:1 mass ratio.
[0045] The furnace lining adopts a multi-layer composite structure, which consists of high-alumina bricks, lightweight clay bricks, and rock wool insulation felt from the inside to the outside. The thickness ratio of each layer is 1:1.5:2, and high-temperature resistant adhesive is applied at the joints between high-alumina bricks and lightweight clay bricks.
[0046] After melting, the fiberization step begins. The glass liquid is fiberized by centrifugal blowing. The centrifugal disk speed is controlled at 5200-6200 rpm, and the blowing pressure is maintained at 0.35-0.55 MPa. At the same time, a circular air distribution plate is set in the blowing area, and ventilation holes with a diameter of 3-5 mm are distributed on the air distribution plate to promote the stable fiberization of the glass liquid under the action of uniform airflow.
[0047] The centrifugal disc is made of nickel-based high-temperature alloy, and its surface is electrolytically polished with a surface roughness Ra < 0.5 microns. A guide groove is set on the edge of the centrifugal disc with a depth of 3-5 mm to ensure that the glass liquid is thrown out evenly.
[0048] In the fiberization process, the sprayed gas is purified air preheated to 220-320℃, and the humidity of the sprayed gas is controlled at 5%-10%. It is first filtered through a ceramic filter with a pore size of 0.1-0.3 microns to create a stable and clean gas phase environment for fiber forming.
[0049] After the fiberization treatment, the cotton collection and molding step is followed. Through negative pressure suction, the fiberized glass wool is collected on the uniformly moving molding mesh belt. The molding mesh belt speed is set to 6-12 meters per minute. The surface of the molding mesh belt has a micro-pit texture with a pit diameter of 0.5-1 mm, which increases the friction between the glass wool and the mesh belt and facilitates uniform adhesion. An adjustable angle wind knife is set under the molding mesh belt. The air flow temperature of the wind knife is 80-120℃, which fine-tunes the distribution of glass wool fibers and further improves the molding uniformity.
[0050] In step S2.
[0051] Specifically, when used, the present invention controls the quality of raw materials from the source, and removes various impurities through pretreatment such as screening, magnetic separation, cleaning and drying, so that the raw materials are pure and have uniform particle size. In the mixing and stirring stage, specific temperature, rotation speed, blade structure and inert gas protection are utilized to achieve deep and uniform mixing of the raw materials. During melting, precise heating parameters and flux addition, combined with high-quality furnace lining, ensure the homogeneity of the glass liquid. In the fiberization stage, with the help of optimized centrifugal disks, blowing parameters and clean preheating gas, fibers of uniform thickness are generated. Finally, in the cotton collection and molding stage, the mesh belt and wind knife are coordinated to make the glass wool evenly formed. All links work closely together to comprehensively improve the uniformity of the glass wool.
[0052] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A production process for improving the uniformity of glass wool, characterized by: The steps include: S1. Raw material selection: Weigh silica sand, soda ash, borax, alumina, and broken glass as basic raw materials. The purity of the selected silica sand is not less than 95%, the purity of soda ash is not less than 98%, the purity of borax is not less than 96%, the purity of alumina is not less than 97%, and the broken glass has no obvious discoloration and impurity agglomeration phenomenon; S2. Preliminary screening: Place the silica sand raw material on a vibrating screen and select a sieve for the first screening to remove large particle impurities and agglomerates whose particle size is larger than the sieve aperture; screen soda ash, borax, alumina, and broken glass; S3. Magnetic separation and impurity removal: The various raw materials that have been preliminarily screened are transported to the magnetic separator in sequence to adsorb and remove the mixed magnetic metal impurities in the raw materials to ensure the chemical purity of the raw materials; S4. Cleaning step: Place the raw materials after magnetic separation in separate cleaning tanks, pour deionized water as the cleaning liquid, and control the mass ratio of deionized water to each raw material at 4:
1. Turn on the stirring device for stirring, and apply ultrasonic cleaning to remove dust, salt and non-magnetic impurities attached to the surface of the raw materials; S4. After cleaning, the wet raw material is transferred to a hot air drying oven for moisture drying, thereby completing the raw material pretreatment; S5. The silica sand, soda ash, borax, alumina and broken glass raw materials that have undergone the raw material pretreatment step are uniformly and accurately fed into a closed stirring kettle with heating and stirring functions through an automated material conveying system according to a predetermined ratio; S6. Heating: Turn on the heating device of the stirring tank to steadily increase the temperature inside the stirring tank until it reaches 280-330°C. This heating process is monitored by a temperature sensor; S7. Agitation operation: When the temperature stabilizes, start the agitator blades of the agitator to rotate at a constant speed for continuous agitation. During the mixing and agitation process, continuously introduce inert gas into the agitator to maintain a slightly positive pressure environment in the agitator, with the pressure value being 0.01-0.03MPa higher than the external environment.
2. A process for improving the uniformity of glass wool according to claim 1, characterized in that: In step S7, the surface of the stirring blade is covered with a ceramic wear-resistant coating with a thickness of 0.3-0.7 mm. The raw materials of the coating include silicon carbide and titanium dioxide with a mass ratio of 3:
1. The coating is attached to the blade by a plasma spraying process.
3. A process for improving the uniformity of glass wool according to claim 1, characterized in that: According to step S7, the raw materials that have been stirred and mixed evenly are transported into the furnace. The furnace is heated by gas, and the gas flow rate is accurately controlled at 10-20 cubic meters per hour. The temperature is raised to 1320-1420° C. at a rate of 12-18° C. per minute. A flux accounting for 2%-5% of the total mass of the raw materials is added, and the temperature is kept for 1.8-2.8 hours to fully melt the raw materials into glass liquid. The flux is a mixture of calcium fluoride and potassium nitrate in a mass ratio of 1:
1.
4. A process for improving the uniformity of glass wool according to claim 3, characterized in that: The lining of the furnace adopts a multi-layer composite structure, which includes high-alumina bricks, lightweight clay bricks, and rock wool insulation felt from the inside to the outside. The thickness ratio of each layer is 1:1.5:2, and a high-temperature resistant adhesive is applied at the joints between the high-alumina bricks and the lightweight clay bricks.
5. A process for improving the uniformity of glass wool according to claim 4, characterized in that: After melting is completed, the fiberization treatment step begins. The glass liquid is fiberized using the centrifugal blowing method. The speed of the centrifugal disk is controlled at 5200-6200 rpm, and the blowing air pressure is maintained at 0.35-0.55 MPa. At the same time, a ring-shaped air distribution plate is set in the blowing area, and ventilation holes with a diameter of 3-5 mm are distributed on the air distribution plate.
6. A process for improving the uniformity of glass wool according to claim 5, characterized in that: The centrifugal disc is made of nickel-based high-temperature alloy, and its surface is electrolytically polished, with a surface roughness Ra < 0.5 microns. A guide groove is set on the edge of the centrifugal disc, and the depth of the groove is 3-5 mm.
7. A process for improving the uniformity of glass wool according to claim 6, characterized in that: In the fiberization process, the spraying gas is purified air preheated to 220-320°C, the humidity of the spraying gas is controlled at 5%-10%, and the spraying gas is first filtered through a ceramic filter element with a pore size of 0.1-0.3 microns.
8. A process for improving the uniformity of glass wool according to claim 7, characterized in that: After the fiberization treatment comes the cotton collection and molding step. Through negative pressure suction, the fiberized glass wool is collected onto a uniformly moving molding mesh belt. The molding mesh belt speed is set to 6-12 m / min. The surface of the molding mesh belt has a micro-pit texture with a pit diameter of 0.5-1 mm. An adjustable angle wind knife is set under the molding mesh belt, and the air flow temperature blown out by the wind knife is 80-120°C.
9. The process for improving the uniformity of glass wool according to claim 1, characterized in that: In step S2, the silica sand raw material is screened with a 80-100 mesh screen; the soda ash is screened with a 60-80 mesh screen; the borax is processed with a 100-120 mesh screen; the alumina is screened with a 120-140 mesh screen; and the broken glass is screened with a 40-60 mesh screen.
10. The process for improving the uniformity of glass wool according to claim 1, characterized in that: In step S4, the drying temperature of the drying box is increased from 80°C to 110°C at a heating rate of 5-10°C / min, and kept at 110°C for 10-15 minutes until the moisture content of the raw material is lower than 0.8%.